Composite anticorrosive coating suitable for concrete in marine environment and preparation method of composite anticorrosive coating
By using composite anticorrosion coatings of polyethylene glycol modified epoxy resin and nanozirconia powder in marine environments, the problem of the concrete coating prone to cracking and peeling in marine environments in the prior art is solved, and efficient waterproofing and wear resistance are achieved, extending the service life of the concrete structure.
Patent Information
- Application Number
- CN202510069872.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The concrete protective coating used in the prior art in marine environments is prone to cracking and peeling after long-term exposure, resulting in degradation of structural performance and increased maintenance costs.
Polyethylene glycol modified epoxy resin is used as the coating primer, and nanozirconia powder and fluorine-containing organic silicone compounds are used in the surface layer to form a high-adhesion, waterproof and wear-resistant coating.
It significantly improves the durability and safety of concrete structures, reduces long-term maintenance costs, and extends the service life of the infrastructure.
Smart Images

Figure CN119775864A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete material anti-corrosion, and specifically relates to a composite anti-corrosion coating suitable for concrete in a marine environment and a preparation method thereof. Background Art
[0002] The marine environment, with its extreme natural conditions and complex ecosystem characteristics, poses severe challenges and tests to concrete structures. In the application scenarios of critical infrastructure such as bridges, docks and offshore wind towers, concrete materials need to withstand the erosion of natural weathering for a long time, and at the same time they need to resist the severe corrosion of the salt spray environment, the erosion effect of deep immersion in seawater, the physical wear of the continuous impact of waves, and the complex biochemical erosion caused by marine biological activities. The combined effect of these multiple environmental factors will gradually lead to the gradual erosion of the mortar layer on the surface of the concrete, the corrosion of the internal steel structure will intensify, and then cause a significant degradation of the structural performance. In extreme cases, this degradation will seriously weaken the overall stability of the infrastructure and shorten its expected service life, thus posing a potential threat to public safety that cannot be ignored. Therefore, it is particularly important to develop effective protection technologies and materials for concrete structures in marine environments to meet the above challenges.
[0003] Although there are many concrete protective coatings designed to cope with marine environmental erosion on the market, these technical solutions still face a series of major challenges in practical application. Especially under long-term exposure to the marine environment, most coatings will inevitably have problems such as cracking and peeling. The root cause of this phenomenon lies in the complex interaction of many factors. First, the salt and other chemical components in seawater are highly corrosive and can penetrate into the coating, react chemically with the coating material, causing the coating performance to gradually decline and then form cracks. These chemical reactions not only weaken the structural integrity of the coating, but also reduce its ability to resist external erosion. Secondly, the adhesion between the coating and the concrete surface is one of the key factors affecting the durability of the coating. If the adhesion is insufficient, the coating is easily peeled off from the concrete surface under the influence of external environmental factors, such as the impact of waves and the corrosion of salt spray. This peeling phenomenon not only destroys the integrity of the coating, but also accelerates the corrosion process of the concrete structure. In addition, salt and other dissolved substances in seawater can penetrate between the coating and the substrate through tiny pores or cracks in the coating to form a water film. The presence of this water film further weakens the adhesion between the coating and the substrate and exacerbates the tendency of the coating to peel off. Once the coating is peeled off, the corrosive substances in the seawater will act more directly on the concrete structure, causing more serious corrosion damage.
[0004] In view of this, it is urgent to develop a composite coating with good durability, simple construction, and economical efficiency to improve the durability of marine concrete structures and reduce long-term maintenance costs, thereby providing a safe and reliable protective barrier for marine engineering. Enhancing the durability of concrete structures can significantly extend the service life of infrastructure, effectively reduce the maintenance and replacement costs caused by corrosion, and also play a positive role in the protection and maintenance of the ecological environment.
[0005] Chinese invention patent application CN117165176A discloses a concrete coating and a preparation method thereof, which relates to the technical field of concrete surface protective coating, including a main agent and a curing agent, the weight ratio of the main agent to the curing agent is 7 to 11:1, and the main agent includes a thermally stable resin prepolymer, a pigment filler, a solvent and other additives. The invention optimizes the material formula and epoxy resin modification process, controls the amount ratio of epoxy and hydroxyl substances, reduces the size of the colloid particles in the epoxy emulsion, and thus improves its overall stability, which can largely avoid the increase in particle energy caused by tropical high temperatures, the increase in the probability of mutual collision and the resulting aggregation and fusion that leads to a decrease in the stability of the concrete coating, improves the stability of the concrete coating when stored at high temperatures, and enables it to be stored for a long time without deterioration in the high temperature of the tropical marine environment; at the same time, after coating, a protective protective coating can be formed on the concrete surface, which has a good protective effect on the concrete structure, but the solvent-based coating contains volatile organic compounds (VOCs), which not only pollutes the environment, but may also have adverse effects on human health.
[0006] Chinese invention patent application CN112778874 discloses a marine engineering concrete corrosion-resistant coating and its preparation method, wherein the corrosion-resistant coating is sprayed or brushed on the concrete surface after evenly mixing component A and component B, wherein component A includes by weight: water-based non-ionic epoxy resin, C10-C12 alkyl glycidyl ether, cage-type silsesquioxane, metal powder, magnesium aluminum hydrotalcite, dispersant, defoamer; wherein component B includes by weight: modified aromatic amine curing agent, C10-C12 alkyl glycidyl ether, self-repairing microcapsule, leveling agent, antioxidant, adhesion promoter, and other additives. The corrosion-resistant coating of the invention has excellent adhesion and corrosion resistance, and can realize the self-repairing property of the corrosion-resistant coating and prevent the migration of chloride ions, thereby extending the service life of the concrete structure, and can be widely used in the protection of marine engineering concrete structures. However, the modified aromatic amine curing agent may have certain toxicity, and appropriate protective measures need to be taken.
[0007] Chinese invention patent application CN114315417A discloses a multifunctional coating for marine concrete that resists chlorine and fouling based on oil-injected polydimethylsiloxane, characterized in that a PDMS coating is first successfully applied on the concrete surface, and then dimethyl silicone oil is injected into the PDMS coating on the concrete surface and the micropores inside the concrete at a certain depth to form a coating with dense, hydrophobic, and bionic super-slip properties. The invention also provides a method for preparing the above-mentioned coating. However, PDMS exhibits certain elastic-plastic properties, which may make its stability at the microstructure level less than that of other rigid materials. In the marine environment, when subjected to dynamic loads such as waves and tides, the mechanical properties of the coating may be reduced, thereby affecting its anti-chlorine and anti-fouling functions. Summary of the invention
[0008] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a composite anti-corrosion coating suitable for concrete in a marine environment and a preparation method thereof. The coating of the present invention has relatively low cost, does not cause secondary pollution, and has good durability and safety.
[0009] To achieve the above object, the present invention adopts the following technical solutions: A composite anti-corrosion coating suitable for concrete in a marine environment, the raw materials of which include a coating primer and a coating topcoat; The coating primer adopts polyethylene glycol modified epoxy resin; Calculated by weight, the coating topcoat comprises: 1-5 parts of nano zirconium oxide powder, 0.5-2.5 parts of fluorine-containing organic silicon compound, 100 parts of polyurethane prepolymer, and 20 parts of polyurethane curing agent.
[0010] Preferably, the polyethylene glycol-modified epoxy resin is prepared by mixing 100 parts of epoxy resin and 3 parts of polyethylene glycol, in parts by mass.
[0011] Preferably, the epoxy resin is 6101 epoxy resin with a medium epoxy value.
[0012] Preferably, the polyethylene glycol is PEG200.
[0013] Preferably, the nano zirconium oxide powder is high-purity nano zirconium oxide with an average particle size of 20 nm and a content of ≥99.9%.
[0014] Preferably, the fluorine-containing organosilicon compound is one of perfluorooctyltriethylsilane, perfluorodecyltrimethoxysilane and fluoropropylmethyldimethoxysilane.
[0015] Preferably, the purity of the fluorine-containing organosilicon compound is ≥98% analytically pure.
[0016] Preferably, the polyurethane prepolymer is one of a PTMG type polyurethane prepolymer and a polyurethane diol prepolymer.
[0017] The present invention also provides a method for preparing the composite anti-corrosion coating suitable for concrete in a marine environment as described above, comprising: Apply the coating primer to the clean and dry concrete surface to form a stable base layer; A coating topcoat is applied on the surface of the base layer, and a complete protective shell is formed after curing.
[0018] Preferably, the preparation process of the coating topcoat includes: Adding nano zirconium oxide powder to the polyurethane prepolymer and stirring to evenly disperse the nano zirconium oxide powder to obtain a first mixture; adding the fluorine-containing organosilicon compound to the first mixture and stirring to make the fluorine-containing organosilicon compound evenly distributed to obtain a second mixture; The curing agent is added to the second mixture, stirred evenly and avoiding the generation of bubbles, to obtain the coating topcoat.
[0019] The present invention has the following beneficial effects: The composite anticorrosive coating for concrete in a marine environment includes a coating primer and a coating topcoat, wherein the design principle of the inner layer (i.e., the coating primer) is as follows: modified epoxy resin: as the inner layer material, polyethylene glycol (PEG) is used to modify the epoxy resin to improve the toughness of the epoxy resin, which can penetrate deeply into the microporous structure of the concrete, and the active groups (such as hydroxyl and carboxyl) in the molecules will react chemically with silicate minerals or other active ingredients on the surface of the concrete to form a stable chemical bond on the surface of the concrete, providing excellent adhesion and moisture resistance. The modified epoxy resin in the inner layer can penetrate into the interior of the concrete, fill microcracks and pores, form a dense waterproof barrier, prevent the penetration of salt and water, and effectively inhibit the alkali-aggregate reaction and steel corrosion inside the concrete. The design principle of the surface layer (i.e., the coating topcoat) is as follows: first, polyurethane is selected as the base material of the coating. This material can not only effectively resist physical impact and deformation in the marine environment, but also restore to its original state after being subjected to external forces, ensuring that the integrity of the coating is not damaged. Secondly, nano zirconium oxide particles are selected as reinforcing fillers, which have extremely high hardness and wear resistance. When nano zirconium oxide is evenly dispersed in the coating system, due to its tiny size, it can deeply fill the micropores inside the coating, increase the density of the coating, and effectively prevent the penetration of seawater and other corrosive media. Considering the problem of humid and hot conditions in the marine environment, fluorine-containing organosilicon compounds are also introduced on the surface of the coating. This compound exhibits hydrophobicity because it contains fluorine elements in its molecular chain. It can significantly reduce the surface energy of the coating surface, prompt water droplets to form spheres on its surface, reduce the contact area between water molecules and the coating, and thus greatly improve the waterproof performance of the coating, so that the durability and safety of the coating of the present invention are better. At the same time, the raw materials of the coating of the present invention are simple and easy to obtain, the cost is relatively low, and it will not cause secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the structure of a composite anti-corrosion coating suitable for concrete in a marine environment in an embodiment of the present invention; In the figure, 1-base layer, 2-bottom layer, surface layer. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is described below in conjunction with specific embodiments. Each embodiment is an experimental example and provides real performance test data. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] The present invention proposes an innovative composite coating technology solution, which is specially designed for concrete structures in marine environments, aiming to overcome the shortcomings of existing technologies and provide a comprehensive protection solution. The composite coating includes an inner layer (or bottom layer) and a surface layer. The inner layer uses polyethylene glycol (PEG) modified epoxy resin, and the surface layer uses a polyurethane coating doped with nano-zirconia and fluorinated organosilicon compounds. Among them, the modified epoxy resin in the inner layer can penetrate deeply into the micropores of concrete, form chemical bonds with concrete, and improve adhesion. The nano-zirconia and fluorinated organosilicon compounds in the surface layer work together to significantly improve the durability of the concrete base.
[0023] The composite anticorrosive coating for concrete in marine environment comprises the following raw materials in proportion by weight: 100 parts of epoxy resin, 3 parts of polyethylene glycol, 1-5 parts of nano zirconium oxide powder, 0.5-2.5 parts of fluorine-containing organosilicon compound, 100 parts of polyurethane prepolymer and 20 parts of polyurethane curing agent.
[0024] Among them, the epoxy resin uses 6101 epoxy resin with a medium epoxy value. The external polyethylene glycol uses PEG200 with a lower molecular weight. The purity of the fluorinated organosilicon compound is ≥98% analytically pure, and the fluorinated organosilicon compound uses one of perfluorooctyltriethylsilane, perfluorodecyltrimethoxysilane and trifluoropropylmethyldimethoxysilane. The nano zirconium oxide powder uses high-purity nano zirconium oxide with an average particle size of 20nm and a content of ≥99.9%. The polyurethane prepolymer uses one of PTMG-type polyurethane prepolymer and polyurethane diol prepolymer.
[0025] The method for preparing the composite anti-corrosion coating suitable for concrete in a marine environment of the present invention comprises the following steps: 1) Preparation of inner layer: First, polyethylene glycol and epoxy resin are uniformly mixed to obtain polyethylene glycol-modified epoxy resin. In the present invention, the epoxy resin is modified to enhance the adhesion and chemical corrosion resistance of the epoxy resin to the concrete structure; the polyethylene glycol-modified epoxy resin is coated on a clean and dry concrete surface to form a stable base layer by utilizing the excellent permeability and adhesion of the polyethylene glycol-modified epoxy resin.
[0026] 2) Preparation of the surface layer: Slowly add the nano zirconium oxide powder to the polyurethane prepolymer, use a high-speed disperser or an ultrasonic processor to evenly disperse the nano zirconium oxide powder to avoid agglomeration; then add the fluorine-containing organosilicon compound, stir it again to ensure that the fluorine-containing organosilicon compound is evenly distributed; then add the corresponding polyurethane curing agent to the above mixture, stir it quickly and evenly to avoid the generation of bubbles, and obtain the coating topcoat, and apply the coating topcoat to the bottom layer. Among them, the formed polyurethane acts as an adhesive to firmly combine the nano zirconium oxide particles and the fluorine-containing organosilicon compound to form a continuous and dense protective layer. The nano zirconium oxide particles are present in the surface layer in a uniformly dispersed manner, forming a tiny barrier layer, which effectively prevents the penetration of harmful substances such as moisture and salt. The fluorine-containing organosilicon compound forms a protective film with low surface energy on the surface of the surface layer, which improves the hydrophobicity and anti-pollution properties of the coating. Covering the surface layer of the present invention on the inner layer can provide additional wear resistance, corrosion resistance and weather resistance.
[0027] 3) Curing and post-treatment: According to environmental conditions, properly control the curing time and temperature to ensure that the coating is fully cured and forms a complete protective shell. After curing, carry out necessary surface inspection and repair to ensure the integrity and effectiveness of the coating.
[0028] Through the above design, the composite coating of the present invention can achieve multi-layer protection for concrete structures, which can not only effectively resist the erosion of the marine environment, but also significantly improve the durability and safety of the concrete structure, reduce long-term maintenance costs, and provide reliable protection for marine infrastructure.
[0029] Embodiment 1: The composite anti-corrosion coating of this embodiment suitable for concrete in a marine environment is prepared according to the following components, measured by weight: 100 parts of epoxy resin, 3 parts of polyethylene glycol, 1 part of zirconium oxide, 0.5 parts of perfluorodecyltrimethoxysilane, 100 parts of PTMG-type polyurethane prepolymer, and 20 parts of polyurethane curing agent.
[0030] This embodiment is applicable to the preparation method of the composite anti-corrosion coating of concrete in a marine environment, comprising the following steps: 1) Add 3 parts of polyethylene glycol to 100 parts of epoxy resin and stir for 1 minute to achieve uniformity to obtain a composite coating primer.
[0031] 2) Evenly mix 100 parts of PTMG type polyurethane prepolymer and 20 parts of curing agent; slowly add 1 part of nano-zirconia powder to the above mixture, and use a high-speed disperser to evenly disperse the nano-zirconia powder; then add 0.5 parts of perfluorodecyltrimethoxysilane to the mixture containing nano-zirconium oxide, and stir again to obtain a composite coating primer.
[0032] When in use, first apply the composite coating primer on the concrete surface; then apply the composite coating topcoat on the composite coating primer surface. After curing, the composite coating primer layer and the composite coating topcoat layer together form an anti-corrosion concrete composite coating, wherein the thickness of the composite coating primer layer is controlled at 50-70 μm, and the thickness of the composite coating topcoat layer is controlled at 80-120 μm.
[0033] Embodiment 2: The composite anti-corrosion coating of this embodiment suitable for concrete in a marine environment is prepared according to the following components, measured by weight: 100 parts of epoxy resin, 3 parts of polyethylene glycol, 3 parts of zirconium oxide, 0.5 parts of perfluorodecyltrimethoxysilane, 100 parts of PTMG-type polyurethane prepolymer, and 20 parts of polyurethane curing agent.
[0034] The preparation process of the composite anti-corrosion coating for concrete in a marine environment in this embodiment is the same as that in the embodiment.
[0035] Embodiment 3: The composite anti-corrosion coating for concrete in a marine environment of this embodiment is prepared according to the following components, measured by weight: 100 parts of epoxy resin, 3 parts of polyethylene glycol, 5 parts of zirconium oxide, 0.5 parts of perfluorodecyltrimethoxysilane, 100 parts of PTMG-type polyurethane prepolymer, and 20 parts of polyurethane curing agent.
[0036] The preparation process of the composite anti-corrosion coating for concrete in a marine environment in this embodiment is the same as that in the embodiment.
[0037] Embodiment 4: The composite anti-corrosion coating of this embodiment suitable for concrete in a marine environment is prepared according to the following components, measured by weight: 100 parts of epoxy resin, 3 parts of polyethylene glycol, 1 part of zirconium oxide, 1.5 parts of perfluorodecyltrimethoxysilane, 100 parts of PTMG-type polyurethane prepolymer, and 20 parts of polyurethane curing agent.
[0038] The preparation process of the composite anti-corrosion coating for concrete in a marine environment in this embodiment is the same as that in the embodiment.
[0039] Embodiment 5: The composite anti-corrosion coating of this embodiment suitable for concrete in a marine environment is prepared according to the following components, measured by weight: 100 parts of epoxy resin, 3 parts of polyethylene glycol, 3 parts of zirconium oxide, 1.5 parts of perfluorodecyltrimethoxysilane, 100 parts of PTMG-type polyurethane prepolymer, and 20 parts of polyurethane curing agent.
[0040] The preparation process of the composite anti-corrosion coating for concrete in a marine environment in this embodiment is the same as that in the embodiment.
[0041] Embodiment 6: The composite anti-corrosion coating of this embodiment suitable for concrete in a marine environment is prepared according to the following components, measured by weight: 100 parts of epoxy resin, 3 parts of polyethylene glycol, 5 parts of zirconium oxide, 1.5 parts of perfluorodecyltrimethoxysilane, 100 parts of PTMG-type polyurethane prepolymer, and 20 parts of polyurethane curing agent.
[0042] The preparation process of the composite anti-corrosion coating for concrete in a marine environment in this embodiment is the same as that in the embodiment.
[0043] Embodiment 7: The composite anti-corrosion coating for concrete in a marine environment of this embodiment is prepared according to the following components, measured by weight: 100 parts of epoxy resin, 3 parts of polyethylene glycol, 1 part of zirconium oxide, 2.5 parts of perfluorodecyltrimethoxysilane, 100 parts of PTMG-type polyurethane prepolymer, and 20 parts of polyurethane curing agent.
[0044] The preparation process of the composite anti-corrosion coating for concrete in a marine environment in this embodiment is the same as that in the embodiment.
[0045] Embodiment 8: The composite anti-corrosion coating of this embodiment suitable for concrete in a marine environment is prepared according to the following components, calculated by weight: 100 parts of epoxy resin, 3 parts of polyethylene glycol, 3 parts of zirconium oxide, 2.5 parts of perfluorodecyltrimethoxysilane, 100 parts of PTMG-type polyurethane prepolymer, and 20 parts of polyurethane curing agent.
[0046] The preparation process of the composite anti-corrosion coating for concrete in a marine environment in this embodiment is the same as that in the embodiment.
[0047] Embodiment 9: The composite anti-corrosion coating for concrete in a marine environment of this embodiment is prepared according to the following components, measured by weight: 100 parts of epoxy resin, 3 parts of polyethylene glycol, 5 parts of zirconium oxide, 2.5 parts of perfluorodecyltrimethoxysilane, 100 parts of PTMG-type polyurethane prepolymer, and 20 parts of polyurethane curing agent.
[0048] The preparation process of the composite anti-corrosion coating for concrete in a marine environment in this embodiment is the same as that in the embodiment.
[0049] The present invention adopts a pull-out test method to measure the bonding strength between the coating obtained in the above embodiment and the concrete substrate, and the specific steps are as follows: 1) Sample preparation: Select representative concrete specimens and ensure that the specimen surface is flat and clean. Then evenly apply the developed composite coating material on the specimen surface, and the coating thickness should meet the actual application requirements.
[0050] 2) Test disc installation: After the coating is completely cured, use a special adhesive to firmly stick the metal test disc to the coating surface, ensuring that there are no bubbles or gaps between the test disc and the coating.
[0051] 3) Loading and measurement: Connect the test plate to the pull-out test equipment and gradually increase the tensile force at a constant rate until the coating separates from the concrete substrate. Record the maximum tensile force value at separation.
[0052] 4) Data processing: Calculate the bonding strength between the coating and the substrate based on the maximum tensile force value and the area of the test disc.
[0053] The concrete coatings prepared in Examples 1 to 9 were tested for bonding strength, and the specific results are shown in Table 1: Table 1
[0054] According to the test results shown in Table 1, it can be seen that with the increase in the amount of nano-zirconia, the bonding strength between the surface layer and the bottom layer is significantly improved. This is because the nano-zirconia particles can be more evenly dispersed in the coating, forming more contact points, thereby enhancing the interaction between the surface layer and the bottom layer. Nano-zirconia can effectively fill the tiny gaps in the coating, optimize the microstructure of the coating, and build a stable interface layer between the surface layer and the bottom layer, which helps to significantly improve the bonding strength.
[0055] The concrete coatings prepared in Examples 1 to 9 were coated on concrete for performance testing, and a concrete test block without any surface treatment and with the same curing method was used as blank sample 0. The compressive strength (MPa) data of different embodiments under dry-wet cycle conditions of a simulated seawater solution (a mixed solution of 5wt% sodium chloride, 5wt% sodium sulfate and 90wt% water) are shown in Table 2.
[0056] Table 2
[0057] According to the test results listed in Table 2, it can be seen that the addition of nano-zirconia significantly improves the performance of the coating. It ensures that the sealing of the coating is not damaged. As the first line of defense for concrete, the integrity and sealing of the coating are the key to preventing moisture and other harmful substances from penetrating into the interior of the concrete. Therefore, the addition of nano-zirconia indirectly protects the concrete from erosion by the external environment, thereby maintaining the original compressive strength and other mechanical properties of the concrete.
[0058] On the other hand, fluorinated organosilicon compounds, due to their excellent hydrophobicity, can significantly reduce the penetration of water and salt, effectively preventing problems such as corrosion of steel bars inside concrete. This enables the coating to better prevent the influence of erosion factors such as salt spray, seawater immersion, and wave impact in the marine environment, thereby indirectly maintaining the compressive strength of the concrete. The mass change rate and compressive corrosion resistance coefficient of different embodiments after 150 dry-wet cycles of simulated seawater solution are shown in Table 3.
[0059] Table 3
[0060] According to the data analysis results in Table 3, nano-zirconia can reduce the wear of the concrete surface, thereby delaying the loss of concrete quality. In addition, nano-zirconia particles can form a tiny barrier layer in the coating, which can prevent harmful substances such as moisture and salt in seawater or other water sources from entering the concrete, thereby reducing the change in concrete quality. This protective mechanism not only helps to maintain the mechanical properties of concrete, but also prolongs the service life of concrete.
[0061] In the above technical solution of the present invention, the inner layer adopts modified epoxy resin as primer, which can form a strong chemical bond with the surface of the concrete substrate, not only can it effectively fill the concrete pores, but also can significantly enhance the waterproof and moisture-proof ability of the substrate, and provide reliable support for the subsequent coating layers. In addition, the surface layer of the coating incorporates polyurethane, nano zirconium oxide and fluorine-containing organosilicon compounds. Polyurethane acts as an adhesive to ensure the close bonding between the components of the surface layer. The reuse of nano zirconium oxide may be to further optimize the wear resistance and hardness of the surface layer. More importantly, the addition of fluorine-containing organosilicon compounds gives the coating surface hydrophobicity and chemical stability.
[0062] Fluorine-containing organosilicon compounds can significantly reduce the penetration of water and salt due to their hydrophobicity, effectively preventing problems such as steel corrosion inside concrete, and indirectly reducing the quality loss of concrete. Fluorine-containing organosilicon compounds can also improve the chemical resistance of the coating, reduce the corrosion of harmful substances such as sulfates and chloride ions in seawater on concrete, thereby reducing the quality loss of concrete. At the same time, fluorine-containing organosilicon compounds can also improve the weather resistance of the coating, so that the coating can better prevent the influence of corrosion factors such as salt spray, seawater immersion, and wave impact in the marine environment, and indirectly reduce the quality change of concrete.
[0063] This composite method not only greatly improves the overall performance of the coating system, but also makes it more adaptable to the external environment, especially harsh conditions such as the marine environment.
[0064] By using these materials, not only can the protective function of the coating be enhanced, but the service life of the concrete structure can also be extended, which is especially important for concrete structures used in marine environments.
[0065] It can be seen from the above that the present invention has the following advantages: 1) The modified epoxy resin of the inner layer, as an organic compound, is selected as the base material due to its excellent adhesion, moisture resistance and chemical resistance. It can adhere tightly to the substrate to form a stable interface and provide a solid foundation for the outer layer.
[0066] 2) The combination of nano-zirconia and fluorine-containing organosilicon compounds in the surface layer improves the hardness and wear resistance of the coating, and the fluorine-containing organosilicon compounds enhance the weather resistance and durability of the coating.
[0067] 3) Compared with the prior art, the composite anti-corrosion coating for concrete in a marine environment proposed by the present invention has the characteristics of low cost, convenient construction, strong durability, etc. It can effectively extend the service life of infrastructure and improve the stability and safety of the structure.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A composite anti-corrosion coating suitable for concrete in a marine environment, characterized in that: Its raw materials include coating primer and coating topcoat; The coating primer adopts polyethylene glycol modified epoxy resin; Calculated by weight, the coating topcoat comprises: 1-5 parts of nano zirconium oxide powder, 0.5-2.5 parts of fluorine-containing organic silicon compound, 100 parts of polyurethane prepolymer, and 20 parts of polyurethane curing agent.
2. The composite anti-corrosion coating suitable for concrete in a marine environment according to claim 1, characterized in that: The polyethylene glycol-modified epoxy resin is prepared by mixing 100 parts of epoxy resin and 3 parts of polyethylene glycol in parts by mass.
3. A composite anti-corrosion coating suitable for concrete in a marine environment according to claim 1 or 2, characterized in that: The epoxy resin is 6101 epoxy resin with a medium epoxy value.
4. A composite anti-corrosion coating suitable for concrete in a marine environment according to claim 1 or 2, characterized in that: The polyethylene glycol used is PEG200.
5. The composite anti-corrosion coating suitable for concrete in a marine environment according to claim 1, characterized in that: The nano zirconium oxide powder is high-purity nano zirconium oxide with an average particle size of 20 nm and a content of ≥99.9%.
6. The composite anti-corrosion coating suitable for concrete in a marine environment according to claim 1, characterized in that: The fluorine-containing organic silicon compound is one of perfluorooctyltriethylsilane, perfluorodecyltrimethoxysilane and fluoropropylmethyldimethoxysilane.
7. The composite anti-corrosion coating suitable for concrete in a marine environment according to claim 6, characterized in that: The purity of the fluorine-containing organosilicon compound is ≥98% analytically pure.
8. The composite anti-corrosion coating suitable for concrete in a marine environment according to claim 1, characterized in that: The polyurethane prepolymer is one of a PTMG type polyurethane prepolymer and a polyurethane diol prepolymer.
9. The method for preparing a composite anticorrosive coating for concrete in a marine environment according to any one of claims 1 to 8, characterized in that: include: Apply the coating primer to the clean and dry concrete surface to form a stable base layer; A coating topcoat is applied on the surface of the base layer, and a complete protective shell is formed after curing.
10. The method for preparing a composite anti-corrosion coating suitable for concrete in a marine environment according to claim 9, characterized in that: The preparation process of the coating topcoat comprises: Adding nano zirconium oxide powder to the polyurethane prepolymer and stirring to evenly disperse the nano zirconium oxide powder to obtain a first mixture; adding the fluorine-containing organosilicon compound to the first mixture and stirring to make the fluorine-containing organosilicon compound evenly distributed to obtain a second mixture; The curing agent is added to the second mixture, stirred evenly and avoiding the generation of bubbles, to obtain the coating topcoat.
Citation Information
Patent Citations
Chlorine-resistant antifouling multifunctional coating for marine concrete and preparation method of chlorine-resistant antifouling multifunctional coating
CN114315417A
Concrete coating and preparation method thereof
CN117165176A
Ternary polymerized graphene nanometer anti-corrosion coating and preparation technique
CN107325686A
Anticorrosion coating for marine concrete protection and preparation method and application thereof
CN110256939A
Concrete protective coating and preparation method thereof
CN114773952A
Cited By
Underwater curing anti-corrosion biological coating and preparation method thereof
CN122078003A